2004
DOI: 10.1093/jurban/jth139
|View full text |Cite
|
Sign up to set email alerts
|

Child Pedestrians: The Role of Parental Beliefs and Practices in Promoting Safe Walking in Urban Neighborhoods

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 9 publications
0
37
0
1
Order By: Relevance
“…[1][2][3] This concern contributes to parents' restriction of their children's independent mobility, 1 outdoor play, and active transport in their local neighborhood. 1,4,5 Compared with previous generations, children now spend less time playing outdoors 6,7 and more time engaged in indoor sedentary leisure pursuits at home. 7,8 This suggests that physical activity opportunities are being missed since time spent outdoors is positively associated with physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] This concern contributes to parents' restriction of their children's independent mobility, 1 outdoor play, and active transport in their local neighborhood. 1,4,5 Compared with previous generations, children now spend less time playing outdoors 6,7 and more time engaged in indoor sedentary leisure pursuits at home. 7,8 This suggests that physical activity opportunities are being missed since time spent outdoors is positively associated with physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…These results have been consistent across studies of children, adolescents, adults, and the elderly. [9][10][11][12][13] Neighborhoods with high violence are thought to encourage isolation and therefore inhibit the social support needed to cope with stressful events. 14,15 Adolescents and adults living in violent neighborhoods have a greater risk for mental health disorders.…”
Section: Introductionmentioning
confidence: 99%
“…6,29,[31][32][33] We also found a significant increase in crosswalk usage by adults, but not by seniors. These findings contrast Morrison et al 30 who reported increased use in senior populations after the installation of a zebra crosswalk.…”
Section: Discussionmentioning
confidence: 46%